The output gap and youth unemployment: An analysis based on Okun's law - Mindaugas Butkus; Janina Seputiene (Economies, 2019)
The impact of economic fluctuations on the total unemployment rate is widely studied, however, with respect to age- and gender-specific unemployment, this relationship is not so well examined. We apply the gap version of Okun's law, aiming to estimate youth unemployment rate sensitivity to output deviations from its potential level. Additionally, we aim to compare whether men or women have a higher equilibrium unemployment rate when output is at the potential level. Contrary to most studies on age- and gender-specific Okun's coefficients, which assume that the effect of output on unemployment is homogenous, we allow a different effect to occur, depending on the output gap's sign (positive/negative). The focus of the analysis is on 28 EU countries over the period of 2000-2018. The model is estimated by least squares dummy variable estimator (LSDV), using Prais-Winsten standard errors. We did not find evidence that higher equilibrium unemployment rates are more typical for men or for women. The estimates clearly show the equilibrium level of youth unemployment to be well above that of total unemployment, and this conclusion holds for both genders. We assess greater youth unemployment sensitivity to negative output shock, rather than to positive output shock, but when we take confidence intervals into consideration, this conclusion becomes less obvious.
Keywords: E24; E32; J16; 330; economic fluctuations; European Union; gender; Okun’ s law; youth unemployment